Sex-specific changes in autosomal methylation rate in ageing common terns - Meyer, Britta S.; Moiron, Maria; Caswara, Calvinna; Chow, William; Fedrigo, Olivier; Formenti, Giulio; Haase, Bettina; Howe, Kerstin; Mountcastle, Jacquelyn; Uliano-Silva, Marcela; Wood, Jonathan; Jarvis, Erich D.; et al. (Frontiers in Ecology and Evolution, 2023)
Senescence, an age-related decline in survival and/or reproductive performance, occurs in species across the tree of life. Molecular mechanisms underlying this within-individual phenomenon are still largely unknown, but DNA methylation changes with age are among the candidates. Using a longitudinal approach, we investigated age-specific changes in autosomal methylation of common terns, relatively long-lived migratory seabirds known to show senescence. We collected blood at 1-, 3- and/or 4-year intervals, extracted DNA from the erythrocytes and estimated autosomal DNA methylation by mapping Reduced Representative Bisulfite Sequencing reads to a new reference genome. We found autosomal methylation levels to decrease with age within females, but not males, and no evidence for selective (dis)appearance of birds of either sex in relation to their methylation level. Moreover, although we found positions in the genome to consistently vary in their methylation levels, individuals did not show such strong consistent variance. These results pave the way for studies at the level of genome features or specific positions, which should elucidate the functional consequences of the patterns we observe, and how they translate to the ageing phenotype.